Surgical simulation and applicant perception in otolaryngology residency interviews. (25th April 2018) - Masood, Maheer M.; Stephenson, Elizabeth D.; Farquhar, Douglas R.; Farzal, Zainab; Shah, Parth V.; Buckmire, Robert A.; McClain, Wade G.; Clark, J. Madison; Thorp, Brian D.; Kimple, Adam J.; Ebert, Charles S.; Kilpatrick, Lauren A.; et al.
Abstract : Objective: The traditional resident applicant interview involves multiple oral interviews. The implementation of surgical simulations adds an additional dimension of assessment but can be perceived in a stressful way by applicants. The purpose of this project is to describe low‐fidelity simulations that were implemented for the 2016 to 2017 residency interviews and obtain applicant perception of these simulations. Methods: Six simulation modules were created, which reflected tasks used in six subspecialties within otolaryngology (pediatrics, otology, laryngology, facial plastics, rhinology, and head/neck). Applicants were guided in the procedures by both an attending and resident. Afterward, applicants were anonymously surveyed on their perception of the tasks using a 5‐point Likert scale (1 = Strongly Disagree, 2 = Somewhat Disagree, 3 = Neutral, 4 = Somewhat Agree, 5 = Strongly Agree). Results: A total of 41 applicants were interviewed. The following were measured: enjoyable (98.5% strongly agree, 2.5% somewhat agree; mean: 4.97; 95% confidence interval [CI], 4.92, 5.02), educational (88% strongly agree, 12% somewhat agree; mean: 4.88; 95% CI, 4.78, 4.98), recommended for future use (92.7% strongly agree, 7.3% somewhat agree; mean: 4.93; 95% CI, 4.85, 5.01), and stressful (63.5% strongly disagree, 19.5% somewhat disagree, 17% neutral; mean: 1.54; 95% CI, 1.30, 1.78). Conclusion: Implementation of a low‐fidelity multi‐station surgical simulation experience is feasible in an interview day. Majority of applicants viewed the simulations in a positive manner. Surgical simulations may provide a useful holistic evaluation of an applicant in future interviews, especially if done in a setting that minimizes stress and maximizes the educational experience. Level of Evidence: 2b. Laryngoscope, 2503–2507, 2018